Director modulation of nematic liquid crystal on photosensitive chalcogenide surface. (22nd January 2018) - Golub, P.; Kurioz, Yu.; Sheremet, N.; Trunov, M.; Reznikov, Yu.
ABSTRACT: We report the first observation of light-induced director patterns formation in a planar liquid crystal (LC) cell with photosensitive chalcogenide film As20 Se80 . The angular patterns appear under the irradiation of the chalcogenide surface by Gaussian laser beam through the LC layer was observed. The experimental results are explained in terms of the transfer of heat from the chalcogenide film to the LC after the light absorption in the chalcogenide layer. Light-induced heating causes a change of the birefringence of the LC and, as a result, spatially modulated polarization state in the plane of the chalcogenide layer. Since the chalcogenide film is a photoaligning material, the spatial modulation of the light polarization leads to a formation of the spatially modulated easy orientation axis and the ring structure of the director in the cell. The model of liquid crystal gauss-shape prism was proposed also. We believe that this effect can be applied for development of different optical and electro-optical elements, such as beam shapers, micro-lenses, zone plates, etc.